A magnetic resonance tuning sensor for the MRI detection of biological targets. Issue 11 (November 2018) - Shin, Tae-Hyun; Kang, Sunghwi; Park, Sohyeon; Choi, Jin-sil; Kim, Pan; Cheon, Jinwoo
Abstract Sensors that detect specific molecules of interest in a living organism can be useful tools for studying biological functions and diseases. Here, we provide a protocol for the construction of nanosensors that can noninvasively detect biologically important targets with magnetic resonance imaging (MRI). The key operating principle of these sensors is magnetic resonance tuning (MRET), a distance-dependent phenomenon occurring between a superparamagnetic quencher and a paramagnetic enhancer. The change in distance between the two magnetic components modulates the longitudinal (T 1 ) relaxivity of the enhancer. In this MRET sensor, distance variation is achieved by interactive linkers that undergo binding, cleavage, or folding/unfolding upon their interaction with target molecules. By the modular incorporation of suitable linkers, the MRET sensor can be applied to a wide range of targets. We showcase three examples of MRET sensors for enzymes, nucleic acid sequences, and pH. This protocol comprises three stages: (i) chemical synthesis and surface modification of the quencher, (ii) conjugation with interactive linkers and enhancers, and (iii) MRI sensing of biological targets. The entire procedure takes up to 3 d. This protocol describes the synthesis of magnetic resonance tuning (MRET) sensors. The sensors consist of two magnetic components separated by a linker and can be modularly designed for targets such as enzymes, nucleic acid sequences, and pH values.